Tumour necrosis factor in man: clinical and biological observations. - Selby, P. (Nature Publishing Group, 1987)
Eighteen patients with advanced cancer have been treated intravenously with human recombinant tumour necrosis factor (rhTNF). The drug produced febrile reactions at all doses although these were preventable by steroids and indomethacin. Doses at or above 9 x 10(5) units (400 micrograms)m-2 were associated with hypotension, abnormal liver enzymes, leucopenia and mild renal impairment in a substantial proportion of patients. RhTNF was cleared from plasma with a half life of approximately 20 minutes but non-linear pharmacokinetics lymphoma, improvements in their tumours were recorded. RhTNF was noted to produce rapid increases in serum C-reactive protein concentrations. Endogenous TNF levels were not found to be elevated in 72 cancer patients. TNF deserves further therapeutic evaluation and these observations support its biological importance as an endogenous pyrogen, mediator of acute phase protein responses, and a mediator of endotoxic shock.